Pre-existing mental health disorders and pregnancy. Issue 3 (March 2019) - Schofield, Zena; Kapoor, Dipanwita
Abstract: Mental health conditions are independent risk factors for poor obstetric and neonatal outcomes therefore obstetricians need to be able to manage them well. This review will summarize the management of pre-existing mental health disorders in pregnancy. Explanations will be given as to which women are managed in primary care for their mental health conditions and which women are managed in specialist Perinatal Mental Health Services. When women should be referred to perinatal mental health services is described. The article provides recommendations on the obstetric management of these women as well as information on psychotropic medication in pregnancy and lactation.